Toxicological and biopharmacological investigations of tiger milk mushroom-Lignosus tigris / Kong Boon Hong - Kong, Boon Hong (2018)
The traditional use for the sclerotium of Tiger Milk mushroom (Lignosus spp.) by local Malaysian natives as a cure for a variety of illnesses has been well documented and scientifically validated. Lignosus tigris C.S. Tan, a species of the Tiger Milk mushroom, has been identified recently and successfully cultivated. In the present study, the potential toxicity of the cultivated L. tigris E sclerotia was evaluated using Sprague Dawley (SD) rats in 14-day acute and 28-day sub-acute toxicity studies. Acute toxicity study showed that the sclerotial powder at a single dose of 2000 mg/kg did not cause adverse effects on growth rate, neither hematological and biochemical parameters, nor pathological changes in vital organ tissues. In addition, daily administration of L. tigris E sclerotial powder at three different doses of 250, 500 and 1000 mg/kg for 28 consecutive days did not cause any treatment-related toxicity in the SD rats, as evidenced by the body weight, general behavior, hematological, clinical biochemical, relative organ weights, and histopathological examination on the vital and reproductive organs. Therefore, the noobserved-adverse-effect level (NOAEL) dose for sub-acute toxicity of the L. tigris E sclerotial powder is more than 1000 mg/kg. The nutritional value, chemical composition, antioxidant and cytotoxic activities of the L. tigris E sclerotium were also investigated. The L. tigris E sclerotium is rich in carbohydrate and protein with moderate amounts of dietary fibers and contains nine essential amino acids. The cold water extract (CWE) of the sclerotial powder showed potent antioxidant activity and cytotoxic selectivity on human breast adenocarcinoma (MCF7) cells. Further fractionation of the CWE using Sephadex G-50 chromatography followed by ammonium sulfate precipitation showed iv that the cytotoxic activity of the mushroom extract against MCF7 cells is contributed mainly by the high molecular weight proteins (HMW-P). HMW-P showed selective cytotoxicity against MCF7 cells (IC50 value = 1.17 ± 0.47 µg/mL) through induction of apoptosis mediated by both intrinsic and extrinsic pathways as indicated by an increase in caspase-8 and -9 activities as well as a decrease of Bcl-2 and increase of Bax expression levels. The intraperitoneal administration of HMW-P (5 µg/g of body weight) to mice bearing MCF7 solid tumor successfully suppressed the tumor growth. HMW-P induced cell death in the tumor via apoptosis as high number of apoptotic cells (stained with TUNEL) was detected in the tumor tissue of the treated mice. Mice treated with HMWP, however, showed a significant reduction in body weight but no pathological changes were observed in the vital organs. Separation of proteins of HMW-P on SDS-PAGE followed by LC-MS/MS analysis identified several potential cytotoxic proteins including lectins, serine proteases and a deoxyribonuclease-like protein. L. tigris E deoxyribonuclease-like protein (LTED) was purified from HMW-P using an affinity chromatography and it exhibited selective cytotoxicity against MCF7 cells (IC50 value = 6.57 ± 0.61 µg/mL) through induction of apoptosis. LTED-induced apoptosis occurs probably via the activation of caspase-dependent and caspase-independent pathways as evidenced by an increase in the activities of caspase 3/7, -8 and -9, a decrease of Bcl-2 protein expression and increases in Bax, AIF and endoG protein expressions. These results showed that there is a great potential to develop L. tigris E sclerotia into functional food and as a nutraceutical, as well as a source of novel proteins with therapeutic applications.